Patience as Art to Hide Intolerance, or the Muslim Brotherhood’s Long-term Strategy to Change the Middle East - A. I. Sarabiev (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2019)
Muslim Brotherhood is listed as prohibited organization in a number of countries, including Russia. Nevertheless, in different periods and in different countries of the MENA region it turned out to be well represented in the legal political field. The temporary failures of this largest branch of political Islam of a radical nature have not yet led to a fatal loss of the organization in the competition between different Islamic groups, or to defeat as a result of repression. The author explores the problem of such stability of an extremist organization for many decades. He defends the hypothesis of its longterm strategic action planning along with the accepted tactics of waiting for a convenient moment for the realization of power ambitions. To analyze the strength of the social base, a variant of the deprivation theory is proposed, which was considered in detail in other works of the author. The historical origins of the organization are identified using published as well unpublished archival documents. A historical retrospective substantiates the assumption that a prototype of this structure used to be existed in Istanbul and Damascus back in the period immediately following the Young Turks revolution in the Ottoman Empire. The strongest external factor in the development of MB is emphasized. It is support throughout the history of the movement from forces outside the region, which have seen and continue to see the possibility for themselves of a tactical alliance with the Islamists of this direction to realize their own ideas and pursue their interests in the East.